2017
DOI: 10.2174/1874285801711010063
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Colistin and Rifampin Against Multidrug Resistant Acinetobacter baumannii: A Systematic Review and Meta-Analysis

Abstract: The existence of infections caused by multidrug resistant (MDR) Acinetobacter baumannii is a growing problem because of the difficulty to treat them. We examined the published literature and focused our analysis on the investigation of the synergism of colistin and rifampin against MDR A. baumannii isolates via systematic review and meta-analysis. A systematic literature search was performed using the following 4 databases (PubMed, Scopus, EMBASE and ISI Web of Sciences). The related articles were evaluated du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
(15 reference statements)
0
20
0
1
Order By: Relevance
“…MIC a and MIC b represent the MIC value read from strip A and strip B tests, respectively. A calculated FICI ≤0.5 represented a synergistic effect (22), a value between 0.5-1 represented as an additive effect, a value between 1-4 represented as an indifferent effect, and a value of >4 represented an antagonistic effect (22). Furthermore, the MIC value of each antibiotic was recorded during combination antimicrobial susceptibility tests.…”
Section: Synergy Testmentioning
confidence: 99%
“…MIC a and MIC b represent the MIC value read from strip A and strip B tests, respectively. A calculated FICI ≤0.5 represented a synergistic effect (22), a value between 0.5-1 represented as an additive effect, a value between 1-4 represented as an indifferent effect, and a value of >4 represented an antagonistic effect (22). Furthermore, the MIC value of each antibiotic was recorded during combination antimicrobial susceptibility tests.…”
Section: Synergy Testmentioning
confidence: 99%
“…Combination of antimicrobials offers a potential for increasing antimicrobial treatment efficacy and for reducing resistance evolution [26]. Synergy between colistin and other antibiotics have been reported [27] [28]. We have tested the combinatorial effect of L-thanatin and colistin against colistin-resistant E. coli but only found concentration-dependent additive effect at certain combinations.…”
Section: Discussionmentioning
confidence: 94%
“…Although only two isolates were categorized as susceptible to rifampin, this agent showed synergy with colistin against eleven isolates. It has previously been confirmed that rifampin combined with other antimicrobials (such as colistin, imipenem, ceftazidim, and ofloxacin) may be synergic against some MDR Gram-negative bacteria 21,22…”
Section: Discussionmentioning
confidence: 95%